ҚАРАҚАЛПАҚ БАЛАЛАР ПОЭЗИЯСЫНДА ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДАҒЫ ДИДАКТИКАЛЫҚ ҚОСЫҚЛАРДЫҢ ӨЗГЕШЕЛИКЛЕРИ - Атабаева, Е. (FAN va JAMIYAT, 2023)
The article analyzes didactic songs in the Karakalpak children’s sheria of the period of independence. Also, the ideas of educational and educational importance in these songs are discussed in detail.